Evaluation of tensile strength of painted steel wi local corrosion at structural connections. (February 2021) - Kim, In-Tae; Jeong, Young-Soo; Dao, Duy Kien
Abstract: Steel structures are often protected by paint coating, but the coating easily deteriorates at structural connections because moisture and dust accumulate at the contact. This leads to the local corrosion on the steel members near the contact and a reduction in tensile performance. The corrosion characteristics and tensile strength of steel plates with a concrete block are investigated. Four types of specimens were prepared, and each type had an unpainted area with different lengths away from the contact boundary. An accelerated cyclic corrosion test was conducted for 600 cycles using CCT-I test conditions specified in the ASTM D 6899–03 standard. To analyze the corrosion characteristics, the surface geometry of corroded specimens was measured in 1 mm × 1 mm intervals by an optical 3D measurement system. The average corrosion depth outside the concrete block was proportional to the unpainted area, and the average corrosion depth inside the concrete block was accelerated in unpainted areas. The two average corrosion depths have a power regression relationship, so the average corrosion depth inside the concrete block can be estimated from the average corrosion depth outside it. A simple method for quantitatively defining the residual thickness is proposed in terms of the effective thickness and the residual tensile strength, which can be evaluated using the effective thickness. Compared to previously proposed methods for this purpose, the effective thickness has higher accuracy. Graphical abstract: Unlabelled Image